ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN PADA WARUNG STEAK DI PUNGGAWAN SURAKARTA - Sutarno, Zahriar Setio Laksmono, Alwi Suddin & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to analyze (1) the impact of product quality to customer satisfaction (2) the impact of product quality to the quality of service (3) the effect of price perception on consumer satisfaction. The population of this research is all consumer WS (warung steak) with a total sample of 70 respondents. The technique of collecting data using questionnaires instrument through the stages of testing the validity and reliability first. Test requirements using classic assumption test. Based on the validity of the test showed that all valid instrument and instrument reliability test showed all reliable. Classic assumption test results show that the variable data of this study has been to meet the assumptions implied in the multiple linear regression model that does not happen multicollinearity problem, autocorrelation does not happen, does not happen heteroskedastisitas and normal residual. The conclusion of the hypothesis testing results indicate that the hypothesis (2) can be accepted or proven true, while the hypotheses (1) and (3) not truth.Keywords: product quality, service quality, perceived price, customer satisfaction